O esporte amador em telejornais esportivos locais - Mello, Raul Augusto Ramalho de (2015)
Several changes impact the planet today. Globalization, while at the same time producing real deterritorializations and practically extinguishes the boundaries related to global communication, ends up reinforcing in people the feeling of connection to a certain place. In the midst of this process, the phenomenon of the mediatization expands the possibilities of communication and content sharing through tools settled primarily on the internet. In this context, there is a need to understand how it is the relationship of traditional media at a regional level (being the television, still, the media which has the greatest insertion in the masses) with the societies in which they are located. In this scenario, this thesis aims to analyze the content about amateur sport in sports TV news produced and displayed on broadcast television, in Campina Grande, Paraíba. They are: Globo Esporte, from TV Paraíba, an affiliate of TV Globo; Itararé Esportes, from TV Itararé, an affiliate of TV Cultura; and Super Esportes, from TV Borborema, SBT affiliate. The methodological procedure includes a literature review with regards to aspects of regional television, proximity journalism, sports television journalism, amateur sport and the relation amongst the sport praxis and the various systems (media, financial, cultural etc.) which surround societies. Furthermore, content analysis making it possible an immersion in the contents by classifying the collected material and a better understanding of the context in which the shows are. As data collection technique, interviews were conducted with the editors of the programs. As a result of the work, it was revealed that sports shows, in Campina Grande, give little space to amateur sport, whereas professional football receives a more focused coverage. Furthermore, the contents related to amateur sports praxis present different features in the studied shows. However, the coverage of events as the main source of content and little concern in advertising what is really local, what happens in Campina Grande, are features that deserve to be highlighted. In this regard, it is noticeable that the sports shows produced and shown in TV, in this city, are similar to other products found in traditional media, for they ensure, for various reasons, privileged space to certain actors and give little attention to groups that usually do not reach out to the traditional media, except in special cases.